Teori Semiotika Komunikasi Hadis ala Umberto Eco - Afwadzi, Benny (Mutawatir, 2014)
This article tries to outline the semiotic theory of communication traditions (hadith). This theory is found when doing integration-author of the study interconnect traditions of the Prophet with the theory of communication semiotics Umberto Eco. Semiotic theory of communication traditions include the nine components in the communication process hadith, that source (the Prophet), message I (editorial authentic Prophet), the transmitter (the narrators of hadith), signal I (various editorial traditions verbally), channel (various books of hadith), signal II (various editorial traditions in writing), receiver (reason riwÃ¢yah hadith), message II (single editorial hadith), and destination (reason semiotic). Methods of understanding hadith contained in destination components that implement the method of unlimited semiotics to find the final logical interpreting. One more thing that is important here, that the stored channel noise (interference) communication in the form of transformation from spoken language into written language, which can result in distortion of meaning.